The Effect of Intensive Lactation Counseling on Exclusive Breastfeeding (ASI) for Up to 3 Months at the Paguat Community Health Center (UPTD) - Sukmawati Sukmawati; Anik Sri Purwanti (NAJ Nursing Applied Journal, 2025)
Exclusive breastfeeding during the first six months of life is a key strategy for improving infant health and reducing morbidity and mortality. However, the coverage of exclusive breastfeeding remains suboptimal in many areas, often due to limited maternal knowledge, inadequate support, and insufficient lactation counseling. Intensive lactation counseling is expected to enhance mothers’ understanding, confidence, and commitment to exclusive breastfeeding. This study aimed to analyze the effect of intensive lactation counseling on exclusive breastfeeding practices up to three months postpartum at the Paguat Community Health Center (UPTD). This study employed a pre-experimental design with a one-group pretest–posttest approach. A total of 30 breastfeeding mothers were selected as participants using purposive sampling techniques. Data on exclusive breastfeeding practices were collected before and after the implementation of intensive lactation counseling using structured questionnaires and observation sheets. The counseling intervention was conducted intensively through individualized sessions focusing on breastfeeding techniques, benefits of exclusive breastfeeding, and problem-solving strategies. Data were analyzed using the Wilcoxon signed-rank test with a significance level set at p < 0.05. The results showed a significant effect of intensive lactation counseling on exclusive breastfeeding practices up to three months postpartum. The Wilcoxon signed-rank test yielded a p-value of 0.000, indicating a statistically significant improvement in exclusive breastfeeding behavior after the intervention. In conclusion, intensive lactation counseling has a significant positive effect on exclusive breastfeeding up to three months. Strengthening lactation counseling services at community health centers recommended to improve exclusive breastfeeding coverage and support maternal and infant health outcomes.